INTEGRATED NUTRIENT MANAGEMENT FOR THE PRODUCTIVITY AND QUALITY IMPROVEMENT OF POTATO UNDER IRRIGATED CONDITION - Sarkar, B.; Mondal, S S; Nayek, S S.; Saha, M; Biswas, S. (Potato Journal, 2013)
A study was undertaken during winter seasons 2002-03 and 2003-04 at Kalyani, to evaluate the effect of integrated nutrient management on productivity and quality of potato under irrigated situation. Different levels of chemical fertilizer viz., 0, 50% of recommended dose of fertilizer (RDF), 100% RDF and 150% RDF, organic sources viz., pelleted form of organic manure (Biomax), karanja cake (Enmite) and crop residues were tested. The dry matter accumulation, tuber dry weight, tuber bulking rate and tuber yield were significantly higher under 150% RDF. The increase in tuber yield with 150% RDF over 100% RDF was 2.8%. Increasing level of chemical fertilizer resulted in an increase in ascorbic acid content and reduction in reducing sugar content. Introduction of organic manure significantly improved plant growth which was ultimately reflected in tuber yield and quality. Among the organic sources, performance of pelleted form of organic manure was better.